Thyroid Function and Mood Disorders: A Mendelian Randomization Study - Kuś, Aleksander; Kjaergaard, Alisa D; Marouli, Eirini; Del Greco M, Fabiola; Sterenborg, Rosalie B T M; Chaker, Layal; Peeters, Robin P; Bednarczuk, Tomasz; Åsvold, Bjørn O; Burgess, Stephen; Deloukas, Panos; Teumer, Alexander; et al. (Thyroid (New York, N.Y.), 2021)
Observational studies suggest that even minor variations in thyroid function are associated with the risk of mood disorders, including major depressive disorder (MDD) and bipolar disorder (BD). However, it is unknown whether these associations are causal or not. We used a Mendelian randomization (MR) approach to investigate causal effects of minor variations in thyrotropin (TSH) and free thyroxine (fT4) levels on MDD and BD risk. We performed two-sample MR analyses using data from the largest publicly available genome-wide association studies on normal-range TSH ( = 54,288) and fT4 ( = 49,269) levels, MDD (170,756 cases, 329,443 controls) and BD (20,352 cases, 31,358 controls). Secondary MR analyses investigated the effects of TSH and fT4 levels on specific MDD and BD subtypes. Reverse MR was also performed to assess the effects of MDD and BD on TSH and fT4 levels. There were no associations between genetically predicted TSH and fT4 levels and MDD risk, nor MDD subtypes and minor depressive symptoms. A one standard deviation increase in fT4 levels was nominally associated with an 11% decrease in the overall BD risk (odds ratio [OR] = 0.89, 95% confidence interval [CI] = 0.80-0.98, = 0.022) and a 13% decrease in the BD type 1 risk (OR = 0.87, CI = 0.75-1.00, = 0.047). In the reverse direction, genetic predisposition to MDD and BD was not associated with TSH nor fT4 levels. Variations in normal-range TSH and fT4 levels have no effects on the risk of MDD and its subtypes, and neither on minor depressive symptoms. This indicates that depressive symptoms should not be attributed to minor variations in thyroid function. Borderline associations with BD and BD type 1 risks suggest that further clinical studies should investigate the effect of thyroid hormone treatment in BD.